Distribution and Attack Rate of Spodoptera frugiperda on Maize in Sijunjung District, West Sumatera Province: Distribusi dan Tingkat Serangan Spodoptera frugiperda pada Tanaman Jagung di Kabupaten Sijunjung, Sumatera Barat - Syafria, Syafria; Reflinaldon, Reflinaldon; Nelly, Novri (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2023)
The density and attack rates of Spodoptera frugiperda have been reported in various maize cultivation in Indonesia, but there has never been a report in Sijunjung District, West Sumatra. The research was conducted to study the attack level, density, and distribution of S. frugiperda in Sijunjung District. The study was carried out in March -May 2023 using a survey method in 8 sub-districts in Sijunjung District. The results showed that S. frugiperda had spread and attacked maize crops evenly in Sijunjung District, but the attack rate (26.96%) and density (0.24 individuals) were low. The highest attack was found in Nagari Guguak (88.7%). The high or low rate of attacks is influenced by differences in varieties, planting ages, and maize cultivation techniques. Meanwhile, the density is more influenced by age differences.